2009
DOI: 10.1007/s00330-009-1657-2
|View full text |Cite
|
Sign up to set email alerts
|

Peri-infarct dysfunction in post-myocardial infarction: assessment of 3-T tagged and late enhancement MRI

Abstract: Contractile dysfunction demonstrated by peak strain was correlated with location at different distances from the infarct. In the border zone, contractile deformation was characterised as earlier T-RS, T-CS and T-ES and greater P-CS than in the infarct area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
3
27
1
Order By: Relevance
“…angiotensin converting enzyme inhibitors, beta-blockers), and definitely less pronounced than what was observed in older studies [12,13,24]. Contrary to previous work we could not demonstrate remote myocardial hypertrophy, or increased remote myocardial contractility to compensate for the loss of function in the infarcted myocardium [25][26][27]. Instead, myocardial mass significantly decreased early after acute MI, and to remain unchanged at longer follow-up.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…angiotensin converting enzyme inhibitors, beta-blockers), and definitely less pronounced than what was observed in older studies [12,13,24]. Contrary to previous work we could not demonstrate remote myocardial hypertrophy, or increased remote myocardial contractility to compensate for the loss of function in the infarcted myocardium [25][26][27]. Instead, myocardial mass significantly decreased early after acute MI, and to remain unchanged at longer follow-up.…”
Section: Discussioncontrasting
confidence: 86%
“…Additionally, the presence of MVO, maximum troponin I levels as well as LV mass at baseline independently predicted adverse LV remodelling at 4M and 1Y with decreasing power (Tables 5 and 6). When comparing patients with and without adverse LV remodelling (Table 7), we found that at baseline those with adverse LV remodelling had a larger infarct size (15.2± 9.1 g vs. 27.4±17.8, p=0.01). The LVEDV and LVESV indices at baseline were not different between patients who subsequently developed adverse LV remodelling and those who did not.…”
Section: Predictive Factors Of Adverse LV Remodellingmentioning
confidence: 84%
“…[27][28][29] Our findings suggest that CE-CMR examination of the heterogeneity of the infarct zone may provide valuable insights into the process of LV remodeling.…”
Section: Discussionmentioning
confidence: 80%
“…There is increasing interest in quantification of this peri-infarct zone because (mechanical) characteristics of this area may serve as a substrate for lifethreatening ventricular arrhythmia. 9,21,22,27) According to Yan, et al identification of a distinct infarct core and border zone may also provide prognostic insights into post-MI remodeling. 9) However, most previous CE-CMR studies that investigated the relationship between infarct size and cardiac remodeling did not measure the size of the peri-infarct zone.…”
Section: Discussionmentioning
confidence: 99%
“…Although previously investigated in the chronic ischaemic cardiomyopathy setting [5,6], systematic data following acute ST-segment elevation myocardial infarction (STEMI) is lacking. CMR imaging offers the capability of unparalleled evaluation of ventricular size and function, quantification of infarct size and the degree of microvascular obstruction (MVO).…”
Section: Introductionmentioning
confidence: 99%